Los pasos previos: Notes on cultural and political radicalization following the business career of Jorge Alvarez (1963 - 1970) - Collado, Pablo Daniel (Centro de Investigaciones Socio Históricas. IdIHCS - CONICET. Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2013)
In this article it is reconstructed the path of the businessman and cultural producer Jorge Álvarez between the year 1963 and 1970. The aim is to raise some aspects referred to the relation established between certain models of intellectuality tied to the Argentine version of the cultural "new left" and the resonances that the global trends tied to a wide process of juvenile contesting reached in our country during those years. As well as in good part of the western world, the consolidation in our country of the youth as a social significant actor fed of an heterogeneous universe of circulating elements across renewed mechanisms of the cultural industry and the mass culture. The article appears as a contribution for the incorporation of aspects relatively disregarded in the existing readings on the phenomenon of juvenile radicalization happened in our country in the intersection of the decades of 60 and 70.